Enhancing the Energy Storage Capabilities of Ti3C2Tx MXene Electrodes by Atomic Surface Reduction. (28th September 2021) - Saha, Arka; Shpigel, Netanel; Rosy; Leifer, Nicole; Taragin, Sarah; Sharabani, Tali; Aviv, Hagit; Perelshtein, Ilana; Nessim, Gilbert Daniel; Noked, Malachi; Gogotsi, Yury
Abstract: MXenes are a large class of 2D materials that consist of few‐atoms‐thick layers of transition metal carbides, nitrides, or carbonitrides. The surface functionalization of MXenes has immense implications for their physical, chemical, and electronic properties. However, solution‐phase surface functionalization often leads to structural degradation of the MXene electrodes. Here, a non‐conventional, single‐step atomic surface reduction (ASR) technique is adopted for the surface functionalization of MXene (Ti3 C2 T x ) in an atomic layer deposition reactor using trimethyl aluminum as a volatile reducing precursor. The chemical nature of the modified surface is characterized by X‐ray photoelectron spectroscopy and nuclear magnetic resonance techniques. The electrochemical properties of the surface‐modified MXene are evaluated in acidic and neutral aqueous electrolyte solutions, as well as in conventional Li‐ion and Na‐ion organic electrolytes. A considerable improvement in electrochemical performance is obtained for the treated electrodes in all the examined electrolyte solutions, expressed in superior rate capability and cycling stability compared to those of the non‐treated MXene films. This improved electrochemical performance is attributed to the increased interlayer spacing and modified surface terminations after the ASR process. Abstract : Atomic surface reduction (ASR)—a new concept for surface functionalization of MXene (Ti3 C2 T x ) using ALD techniques. The process results in increased interlayer spacing, modified surface terminations, and improvement in electrochemical performances of ASR‐MXene in acidic and neutral aqueous electrolytes, as well as in conventional Li‐ion and Na‐ion organic electrolytes.